Eksistensi Pendidikan Madrasah Diniyah Dalam Penguatan Hasil Belajar Pendidikan Agama Islam - Nurasiroh, Ai Alin; Sulaeman, Oyib; Aimi, Widi (THORIQOTUNA: Jurnal Pendidikan Islam, 2024)
This study aims to determine how existence Madrasah Diniyah Education toward student learning outcomes in Islamic Religious Education subjects at school. This research uses a descriptive method with a quantitative approach. Samples were taken as many as 22 respondents, using a random sampling technique.This study uses a descriptive method with a quantitative approach. The population of this study was 145 students with a sample of 22 respondents, the sample was taken using random sampling technique. Data collection techniques using questionnaires, interviews and documentation. Quantitative data processing is completed through descriptive data processing with spearman rank correlation. Based on the research results, Madrasah diniyah education data greatly influences student learning outcomes in Islamic education subjects at SMPN 2 Panumbangan. .81 – 0.100, and the results of the calculations obtained the t_count value of 9,6184 while the t_table based on the significant level (α = 0.05) and obtained in the t_table list (0.05) (27) is 1.7032. Thus if t_count ≥ t_table then H_a is accepted and H_o is rejected. Madrasah diniyah education on student learning outcomes in PAI subjects at SMPN 2 Panumbangan is 77,44%, the remaining 22,56% is determined by other factors